Monitoring the diurnal and seasonal foraging of Hawaiian monk seals in mesophotic rubble habitat using seafloor event loggers called ‘electric rocks’ - FA Parrish; RC Boland; M Sawyer; BD Greene; B Buhleier; GJ Marshall (Endangered Species Research, 2023)
Video from cameras fitted to Hawaiian monk seals showed that seals visited patches of loose mesophotic seafloor rock to flip them and obtain the prey hiding underneath. Diver surveys of rock patches documented 38 species of fish and invertebrates and found 38% of the larger diameter rocks (10-100 cm) flipped with the encrusted live coral and algae side left face down. We developed a set of ‘electric rocks’ (artificial rocks fitted with event loggers) to record the date and time of any movement. We deployed the rocks in multiple clusters on the terraced slope of the seal colony atoll (French Frigate Shoals) close to the beach haulout and at 2 sites further away on the summits of neighboring banks. The goal was to expand temporal monitoring (diurnally and seasonally) of the seal’s use of mesophotic rubble patches without requiring further instrumentation of monk seals. The data from the electric rocks showed patterns consistent with the behavior seen from the seal-mounted video, including rapid rock-to-rock searching and more movements closer to seal haulouts. The electric rocks detected more rock tips on the atoll terrace than on the banks, with higher counts seen during the day at the bank summits. Seasonally, both the terrace and bank detected more movements in summer and fall months consistent with the monk seal’s reproductive pupping and molting season than during the rest of the year, suggesting some seasonal change in the foraging habitat of monk seals.